The Determinants of Millennial Interest in Investing on Sharia Securities Crowdfunding Platforms in Indonesia - Iswanti, Rini; Endri, Endri; zaerofi, afif (Tazkia Islamic Finance and Business Review, 2024)
This research aims to analyze the influence of attitude variables, subjective norms, and perceived behavioral control on interest upon investing in SCF sharia as well as the influence of the variables of Islamic financial literacy, religiosity, risk and return on attitudes towards investing among the millennial generation in SCF Syariah. The research employed a quantitative approach utilizing the Structural Equation Model Partial Least Square (SEM-PLS) with primary data gathered through purposive sampling. The technique was conducted by an online method on 152 individuals from the millennial generation. Not all TPB factors significantly influence the interest to invest in Sharia Securities Crowdfunding. Attitude and Behavior Control Perception have a positive impact on the interest to invest in Sharia SCF. Subjective Norm does not have an impact on the interest to invest in Sharia SCF. Sharia financial literacy does not significantly affect attitude. Religiosity significantly affects attitude. Risk and return significantly affect attitude.